Edutraining Koperasi Pada KPRI “Nasib” Kecamatan Butuh Kabupaten Purworejo - Supriono, Supriono; Widiyohening, Caecilia Rosma; Ayuningtyas, Pratika (LPPM Universitas Flores, 2023)
Cooperatives are business entities that aim to improve the welfare of their members. KPRI